Large African Hive Beetle Oplostomus fuligineus (Olivier) (Insecta: Coleoptera: Scarabaeidae) - Worrel Ashley Diedrick; Cameron Jack (EDIS)
This article is also published on the Featured Creatures website at http://entnemdept.ufl.edu/creatures/misc/bees/large_African_hive_beetle.htm